STUDY ON THE IMPLEMENTATION OF RAINWATER HARVESTING AND THE EFFECT OF CHANGING STUDENTS ATTITUDES IN KIDANG PANANJUNG DORMITORY OF BANDUNG INSTITUTE OF TECHNOLOGY - Maria Tumurang, Olivia
Floods are the seasonal threat that always occurs, an increase in surface flow discharge that has the effect of flooding due to loss absorption capacity so that drought disasters increase in the dry season. Techniques or methods are needed to prevent this, such as the concept of ecodrainage that can be applied, among others, is Rainwater Harvesting (RWH). The participation of the community in terms of maintenance is needed to maintain the success of the ecodrainage system. The community here are students of the Kidang Pananjung Dormitory of the Bandung Institute of Technology who have the potential to support the maintenance of the ecodrainage system. With the hope that students who have lived in the ITB Dormitory can provide examples of environmental maintenance that have been carried out by ITB Dormitory to be applied in their respective homes in overcoming the probability of flooding. This study evaluates the application of the rainwater harvesting system and the participation of boarding-house students in the ITB Kidang Pananjung Dormitory in managing Environmental-Based Drainage. The method used to calculate the capacity of rainwater harvesting facilities uses a monthly storage simulation. Rain distribution uses the Log Pearson Type III Frequency Analysis Method. Frequency distribution testing uses the Smirnov-Kolmogorov Method for horizontal testing and Chi-square method for vertical testing. The approach was taken to see the changing attitudes of ITB students at Kidang Pananjung Dormitory in maintaining rainwater harvesting systems using the Theory of Planned Behavior. The potential of rainwater that can be stored by the rainwater harvesting system at ITB Kidang Pananjung Dormitory is 41,850 liters for a year. The lack of rainfall in July and August caused a water shortage of 795 liters. The dimension of the gutter that is already installed is 15 x 15 cm which produces a discharge with a value of 0.021 m3/s. It can be used until the 10 year return period. The use of the Theory of Planned Behavior approach explains that students of the Kidang Pananjung Dormitory of the Bandung Institute of Technology tend to need more encouragement and support from others in maintaining and implementing rainwater harvesting systems, and behavior control from other parties who will provide them with ease and difficulty in maintaining and implementing rainwater harvesting systems. Students are still not aware that maintaining and implementing a rainwater harvesting system is a positive thing to do and implement.